Avaliação do potencial de recuperação oocitária, produção de embrião e gestação em doadoras da raça GIR - Oliveira, Eduardo Ramos de (2011)
The production of bovine embryos had a pronounced increase in the last decade. In Brazil, this increase was directly related to the improvement of the in vitro embryo production, particularly in dairy cattle. The present experiment used the transvaginal ultrasound-guide for ovarian follicle aspiration (TGFA) and in vitro embryo production in Gyr cattle (dairy zebu breed) to assess the potential of the donator for oocyte and embryo production. Data from a private company (Biotran Alfenas, MG - Brazil), recovered for the last three years were included in this study. Cows were supplemented with corn silage and a mixture of corn, soybean, vitamin and minerals, according to their nutritional requirements. The ovarian follicular wave was synchronized 5 days before TGFA. Briefly, auricular implant and intramuscular injections of 3 mg of estradiol benzoate and 0.530 mg of sodium cloprostenol. The TGFAs were performed according to the same basic procedures: using the ultrasound device (Pie-Medical Esaot Akila) and a vacuum system (pressure of 80 mmHg) with a disposable 20G needle in one extremity and a collector tube (50 ml) in the other. Only TGFAs with at least one oocyte recovered were considered, and a total of 178 TGFAs sessions from different Gyr cows (≥ 60 days after parturition) were used. The recovered oocytes were classified according to the cumulus cells layers and cytoplasm aspect. Sex-sorted (X) semen with proved fertility was used for in vitro fertilization and embryo production. According to the total recovered oocytes the cows were ordered in one of the 4 quartiles, with the top 25% (1st quartile), the median 50% (2nd and 3rd) and the bottom 25% (4th quartile). The average of recovered oocyte (total, viable and unviable), total embryo and the number of pregnancies produced in each TGFA session were compared between the first and the fourth quartiles. Conversion rates (%) of the total and viable oocytes to embryo, viable oocytes to pregnancy and embryo to pregnancy were also performed. Data were analyzed by one-way ANOVA (9.2 Version; SAS Institute Inc., Cary, NC, USA). Differences between the first and fourth quartiles were accessed by Student s t-test and frequency data were evaluated by Fisher s Exact test. The production of oocytes and embryos, and the number of pregnancies (mean ± SD by session) were higher (P< 0.0001) in the animals of the first quartile (41.6 ± 10.6 vs 6.7 ± 3.1 oocytes; 29.1 ± 11.0 vs 4.5 ± 2.7 viable; 8.6 ± 5.7 vs 1.8 ± 1.8 embryos). The rate of pregnancy was 46.0%, 44.9%, 43.9% and 45.6% for the I; II; III and IV respective. The conversion rate of the viable oocytes to embryo was greater (P< 0.03) in animals from the fourth quartile (51.1 vs 31.9%). The interpretation was that for Gyr breed the animals with high donator potential produce in average 40 viable oocytes and 8 embryos in each session of the TGFA. The data suggest that the selection of the animals with high potential for oocyte production can improve the absolute but not relative number of the in vitro embryos produce.